Heterogeneous effects of financial development on renewable energy consumption: Evidence from global dynamic panel threshold approach - Muhammad Tariq Majeed; Zubia Hussain (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
A transition from conventional energy sources to renewable energy (RE) sources remains an important concern of the present world. This transition, however, largely depends upon financial sources required for start-up investments, operating costs, and advanced infrastructure. However, an important question arises as to what is the threshold level of financial development (FD) that can boost RE consumption. To answer this, the present study empirically investigates the relationship between FD and RE consumption considering the nonlinear effects of FD. The study used broad money, domestic credit to the private sector, and domestic credit to the private sector by banks as proxy variables of FD from 1970 to 2020 at a global level of 173 countries. The study employed the econometric techniques of pooled OLS method, fixed effects, random effects, and Driscoll and Kraay regression. Additionally, the dynamic panel threshold technique is utilized to obtain the threshold value of FD for robust and reliable analysis. The analysis confirmed the presence of a U-shaped association between FD and RE consumption. The results suggest that all measures of FD boost RE consumption after reaching a certain threshold level of FD. Moreover, economic growth, urbanization, industrialization, and trade showed a significant impact on RE consumption. The study offers unique insights on threshold values of alternative measures of FD for environmental policy designs.
Keywords: 330; Financial development; renewable energy consumption; scale effect; technique effect; threshold variable; dynamic panel threshold regression; urbanization; industrialization